Cultivo e extração de óleo das microalqas Scenedesmus sp. E Spirulina sp. para a síntese de ésteres visando à produção de biodiesel - Baumgartner, Tatiana Rodrigues da Silva (2011)
Within a global segment by search for renewable energy, biofuels emerged as a viable alternative to fossil fuels, biodiesel is a promising successor to diesel. The search for new raw materials for biodiesel production has gained high profile in recent years, the microalgae are considered potentially useful for this process. These photosynthetic microorganisms use solar energy associated with water and carbon dioxide to produce biomass that can be transformed into available energy, such as biodiesel. Thus, the thesis aimed to study the cultivation of microalgae of the genus Scenedesmus sp. and Spirulina sp., the oil extraction and the production of methylic and ethylic esters seeking at biodiesel production, by in situ reaction and by acid transesterification/esterification reaction of oil. From the results obtained with the extraction, it was observed that the solvent features may favor one or another biomass component. The fatty acid of oil profile from microalgae Scenedesmus sp. showed higher proportion of long chain fatty acid than the microalgae Spirulina sp., both with high acidity, 4,9 from Scenedemus sp. and 14,3 from Spirulina sp. In the production of esters for both the microalgae Scenedesmus sp. as for Spirulina sp., factorial analyzes of variance, revealed that there was an interaction between the four factors (p<0.05): temperature, time, alcohol and solvent. The interactions that led on average to higher incomes for microalgae Scenedesmus sp. were chloroform and ethanol (T=60 °C), methanol and chloroform (T=60 °C) and ethanol and hexane (T=60 and 90 °C). The reactions with Spirulina sp., interactions that led, on average, at higher yields were chloroform and ethanol (T=60 °C) and ethanol and hexane (T=45 °C). There was difference in transesterification/esterification reactions in situ between the two microalgae examined, possibly due to differences in the cellular structure of microalgae. In acid transesterification/esterification reactions of microalgae oil was obtained a theoretical yield of ester 10 to 15 times lower when compared with the reaction in situ.esters in high yields.